Cultivating Moral Competence of Chinese Undergraduates with KMDD-Sessions - Zhang, Jing (ETHICS IN PROGRESS, 2013)
This study describes the results of interventions with the Konstanz Method of Dilemma Discussion (KMDD) by Georg Lind, with 89 economics undergraduate participants sampled from Guangdong province. The participants’ mean C-score in the Moral Judgment Test increased only a little because of the teacher’s little experience in using KMDD, but otherwise the intervention produced good results: the participants showed great interest in KMDD although this teaching method is very different from the typical Chinese teaching, and they enjoyed the KMDD-sessions and the classroom atmosphere created through it. Students’ feedback will be useful for future application and research on KMDD in China.